Application of the ground cooling system for rural houses air conditioning in northeastern China - Jang, Moon Ki (International Journal of Agricultural and Biological Engineering, 2022)
This study developed an appropriate ground cooling system that can be used for indoor cooling during summers in rural houses in northeastern China. To apply this system, a traditional rural house was selected and a heat exchanger was designed (PE pipe, 32 m in length), manufactured, and installed according to the cooling load (2206 kJ/h) of one room of the experimental house. According to the experiment, the temperature of Room 1 equipped with the cooling system was 3°C lower than that of Room 2 without the ground cooling system during the same time period. The temperature reduction effect of this system was confirmed through this study. When the ground cooling system was used in rural houses in Northeast China, it was found that a burial depth of 1.5-2.0 m for the ground heat exchanger is appropriate for considering workability and frost line. The use of the ground cooling system for indoor cooling during summers for rural houses in the northeastern region of China would reduce not only environmental pollution and the use of fossil fuels but also ease farmers off a certain amount of financial burden. Keywords: ground cooling system, ground heat exchanger, air conditioning system, rural houses DOI: 10.25165/j.ijabe.20221502.6223 Citation: Jang M K. Application of the ground cooling system for rural houses air conditioning in northeastern China. Int J Agric & Biol Eng, 2022; 15(2): 230–235.